High preoperative plasma vasohibin‐1 concentration predicts better prognosis in patients with non–small cell lung carcinoma. Issue 6 (17th May 2018) - Watanabe, Tatsuaki; Hosaka, Tomoko; Ohmori‐Matsuda, Kaori; Suzuki, Yasuhiro; Suzuki, Hirotoshi; Yabuki, Hiroshi; Matsuda, Yasushi; Noda, Masafumi; Sakurada, Akira; Okada, Yoshinori; Sato, Yasufumi
Abstract: Background and Aim: Vasohibin‐1 (VASH1) is an angiogenesis inhibitor synthesized and secreted by endothelial cells, whose expression is induced by angiogenic stimuli such as vascular endothelial growth factor. We have previously demonstrated that VASH1 is immunohistochemically evident in endothelial cells in the tumor microenvironment of patients with non–small cell lung cancer (NSCLC) and is positively correlated with that of vascular endothelial growth factor in cancer cells. Here, we determined the preoperative plasma concentration of VASH1 in patients with NSCLC and evaluated the association between the preoperative VASH1 levels and certain outcomes. Methods: We analyzed presurgical plasma VASH1 concentrations in a total of 79 lung cancer patients (51 males and 28 females; 34‐83 y of age; 46 adenocarcinomas, 27 squamous cell carcinomas, and 6 other types) who underwent lung resection. The impact of preoperative VASH1 level was analyzed using clinical characteristics and prognosis. Results: Plasma VASH1 concentration ranged from 34.1 to 1190.4 fmol/mL. We divided the patients into 3 groups according to plasma VASH1 level for this assessment: low VASH1 group (n = 26), medium VASH1 group (n = 27), and high VASH1 group (n = 26). The death and recurrence rates of the high, medium, and low VASH1 groups were 5.5, 16.2, and 12.7 per 100 person‐years, respectively. Multivariate adjusted hazard ratio of death and recurrence of the high VASH1 group was lower than that of the low VASH1 group (hazard ratio 0.42; 95% CI 0.17‐0.99). Conclusion: The present analysis suggests that high preoperative plasma VASH1 concentration is associated with better prognosis in patients with NSCLC. We propose preoperative VASH1 level as a biomarker for the prognosis of patients with non–small cell lung carcinoma. Abstract : Background and Aim: Vasohibin‐1 (VASH1) is an angiogenesis inhibitor synthesized and secreted by endothelial cells, whose expression is induced by angiogenic stimuli such as vascular endothelial growth factor. We have previously demonstrated that VASH1 is immunohistochemically evident in endothelial cells in the tumor microenvironment of patients with non–small cell lung cancer (NSCLC) and is positively correlated with that of vascular endothelial growth factor in cancer cells. Here, we determined the preoperative plasma concentration of VASH1 in patients with NSCLC and evaluated the association between the preoperative VASH1 levels and certain outcomes. Methods: We analyzed presurgical plasma VASH1 concentrations in a total of 79 lung cancer patients (51 males and 28 females; 34‐83 y of age; 46 adenocarcinomas, 27 squamous cell carcinomas, and 6 other types) who underwent lung resection. The impact of preoperative VASH1 level was analyzed using clinical characteristics and prognosis. Results: Plasma VASH1 concentration ranged from 34.1 to 1190.4 fmol/mL. We divided the patients into 3 groups according to plasma VASH1 level for this assessment: low VASH1 group (n = 26), medium VASH1 group (n = 27), and high VASH1 group (n = 26). The death and recurrence rates of the high, medium, and low VASH1 groups were 5.5, 16.2, and 12.7 per 100 person‐years, respectively. Multivariate adjusted hazard ratio of death and recurrence of the high VASH1 group was lower than that of the low VASH1 group (hazard ratio 0.42; 95% CI 0.17‐0.99). Conclusion: The present analysis suggests that high preoperative plasma VASH1 concentration is associated with better prognosis in patients with NSCLC. We propose preoperative VASH1 level as a biomarker for the prognosis of patients with non–small cell lung carcinoma.